2005
DOI: 10.1080/014850190924520
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Cell Phone Use and Semen Quality?

Abstract: This study was conducted to determine a possible relationship between regular cell phone use and different human semen attributes. The history-taking of men in our university clinic was supplemented with questions concerning cell phone use habits, including possession, daily standby position and daily transmission times. Semen analyses were performed by conventional methods. Statistics were calculated with SPSS statistical software. A total of 371 were included in the study. The duration of possession and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
7
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 26 publications
6
143
7
8
Order By: Relevance
“…Various studies have recently expounded on the possible influence of RF-EMF on DNA integrity of male germ cells [Aitken et al, 2005] as well as on sperm motility [Davoudi et al, 2002;Fejes et al, 2005;Erogul et al, 2006]. As with so many studies conducted in this field, some of the findings were criticized due to a lack of dosimetry and not taking confounding risk factors into account [European fast response team on EMF and Health, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have recently expounded on the possible influence of RF-EMF on DNA integrity of male germ cells [Aitken et al, 2005] as well as on sperm motility [Davoudi et al, 2002;Fejes et al, 2005;Erogul et al, 2006]. As with so many studies conducted in this field, some of the findings were criticized due to a lack of dosimetry and not taking confounding risk factors into account [European fast response team on EMF and Health, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have highlighted the possibility that RF-EMF could influence sperm motility [Davoudi et al, 2002;Fejes et al, 2005;Kilgallon and Simmons, 2005;Erogul et al, 2006]. Motility is a pre-requisite in the journey of spermatozoa to the oocyte eventuating in hyperactivated motility, which is required for sperm penetration of the zona pellucida [Yanagimachi, 1994;de Lamirande et al, 1997;Ho and Suarez, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another retrospective study also stated that the duration of mobile phone use and daily transmission also create negative effect on motility [13]. This study proves that there is no effect found on the sperm motility quality when the sperm group was treated with 3 hours of radiation.…”
Section: H H Syam Et Almentioning
confidence: 49%
“…The second cause is that the electromagnetic radiation from mobile phones can directly cause DNA damage in the male genital tract cells [13]. Men are susceptible to decreased sperm quality due to mobile phone use because men often put their cell phone in their trousers' pocket when they do their daily activities.…”
Section: /9mentioning
confidence: 99%
“…Mobile phone radiation exposure limits are based on thermal heating of the body and the brain [4]. Many research studies have identified biological effects far below the thermally based exposure limits, such as increased permeability of the blood-brain barrier in the head [5], deleterious effects on sperm [6][7][8], double strand breaks in DNA [9], and stress gene activation indicating an exposure to a toxin, [10]. Other studies have pointed at an increasing risk of acoustic neuroma and brain cancer after several years of cell phone use [11][12], and especially so in more sparsely populated regions where the output power from cell phones generally is increased compared with that in a city region in close contact to base stations, [13][14].…”
Section: Introduction Backgroundmentioning
confidence: 99%